A Participatory Interior Design Approach for a Restorative Work Environment: A Research-Intervention - Pasini, Margherita; Brondino, Margherita; Trombin, Rita; Filippi, Zeno (Frontiers in Psychology, 2021)
Exposure to environmental stressors has physical and psychological consequences. A demanding physical environment involves the allocation of additional attentional resources and an increase in psycho-physical stress. This study illustrates the process of a research-intervention aimed at designing a workplace, using a participatory design approach, and considering the beneficial effect of restorative environments in reducing stressful elements and improving wellbeing at work. Stressful situations occur daily, compromising proper functioning while causing the occurrence of physiological and/or psychological disorders (Baroni & Berto, 2013). To be able to safeguard their psycho-physical wellbeing, people normally adopt coping strategies, i.e., remedies that allow them to cope and manage situations that generate stress. One of these strategies is the exposure to natural environments, which promotes recovery and sustains psycho-physical wellbeing. The restorative properties of natural environments have been scientifically proven (Menardo et al., 2019). However, even built spaces can be thought of as restorative environments (Ulrich, 1983; Kaplan, 1995; Berto et al., 2015), in particular when certain conditions are granted. An applied science, known as biophilic design, provides useful indications from this perspective. This project involved 57 employees of the Italian site of an international non-governmental organization, in the transition from a site no longer adequate to a new site requiring renovation. In a first phase, a survey was conducted, to verify the perceived quality of the current workplace and to detect the unmet workers’ needs, and to assess some other important psychological constructs connected with perception of restorativeness and wellbeing. In a second phase, the findings emerged from the survey was analyzed in depth through a participatory interior design process, together with an interdisciplinary team of architects, technicians of the organization and environmental psychology researchers. The team, together with some representatives of employees, worked together through possible scenarios, adopting a biophilic design approach, to design the new workplace. At the end, the same survey of the first phase was conducted, to detect differences in perceived quality in the new workplace compared to the previous one.